De novo assembly of a transcriptome for Calanus finmarchicus (Crustacea, Copepoda)--the dominant zooplankter of the North Atlantic Ocean. - Petra H Lenz; Vittoria Roncalli; R Patrick Hassett; Le-Shin Wu; Matthew C Cieslak; Daniel K Hartline; Andrew E Christie (PLoS ONE)
Assessing the impact of global warming on the food web of the North Atlantic will require difficult-to-obtain physiological data on a key copepod crustacean, Calanus finmarchicus. The de novo transcriptome presented here represents a new resource for acquiring such data. It was produced from multiplexed gene libraries using RNA collected from six developmental stages: embryo, early nauplius (NI-II), late nauplius (NV-VI), early copepodite (CI-II), late copepodite (CV) and adult (CVI) female. Over 400,000,000 paired-end reads (100 base-pairs long) were sequenced on an Illumina instrument, and assembled into 206,041 contigs using Trinity software. Coverage was estimated to be at least 65%. A reference transcriptome comprising 96,090 unique components ("comps") was annotated using Blast2GO. 40% of the comps had significant blast hits. 11% of the comps were successfully annotated with gene ontology (GO) terms. Expression of many comps was found to be near zero in one or more developmental stages suggesting that 35 to 48% of the transcriptome is "silent" at any given life stage. Transcripts involved in lipid biosynthesis pathways, critical for the C. finmarchicus life cycle, were identified and their expression pattern during development was examined. Relative expression of three transcripts suggests wax ester biosynthesis in late copepodites, but triacylglyceride biosynthesis in adult females. Two of these transcripts may be involved in the preparatory phase of diapause. A key environmental challenge for C. finmarchicus is the seasonal exposure to the dinoflagellate Alexandrium fundyense with high concentrations of saxitoxins, neurotoxins that block voltage-gated sodium channels. Multiple contigs encoding putative voltage-gated sodium channels were identified. They appeared to be the result of both alternate splicing and gene duplication. This is the first report of multiple NaV1 genes in a protostome. These data provide new insights into the transcriptome and physiology of this environmentally important zooplankter.